Eunotia rudis sp. nov., a new diatom (Bacillariophyta) from the Man and Biosphere Reserve at Yangambi, Democratic Republic of the Congo - Cocquyt, Christine; Haan, Myriam De; Ndjombo, Edit Lokele (Phytotaxa, 2016)
Eunotia rudis sp. nov. is described from material collected in acid rivers in an almost pristine tropical rain forest in the Congo Basin in Central Africa. The benthic diatom community was dominated by other Eunotia spp. and small naviculoid taxa. The morphological features of the new species are described and documented based on light and scanning electron microscopy investigations. Eunotia rudis sp. nov. can be distinguished from other taxa within the genus Eunotia by its typical slightly asymmetric valve shape with four dorsal undulations and the rough surface of the thick silica wall. In contrast to other Eunotia species, the number of dorsal undulations was constant in all observed populations. Differences between the new species and the related Eunotia garucisa and E. garucisa var. polydentula are discussed.